Effect of Sustainability Report Disclosure on Banking Company Value - Onggu, Aulia Raddin; Abidin, Zaenal (PT. Riset Press International, 2023)
The purpose of this study is to evaluate how disclosure of Sustainability Report, disclosure of economic performance, disclosure of environmental performance, and disclosure of social performance affect company value as measured by Tobin's Q. Banking companies at Bank BUKU 3 and Bank BUKU 4 are listed on the Indonesia Stock Exchange from from 2019 to 2021. The population for this study totaled 31 companies with the sample criteria, namely the purposive sampling technique totaling 11 data generated. For analysis, the panel data regression model is used using Eviews 12. The results of the analysis simultaneously show that the sustainability report has no effect on firm value (Tobin's Q). Based on the partial test results, Sustainability Report, economic performance reports, environmental performance reports and social performance reports have no effect on firm value (Tobin's Q). Keywords: Disclosure, Sustainability Report, Corporate Value, Tobin's Q, BUKU 3 and BUKU 4